Hukum Islam Terhadap Pencegahan Perilaku Seks Bebas Pada Remaja Di SMP N 19 Kota Bengkulu - Lussyefrida Yanti; selvia novitasari; Noveriyanto (JURNAL PENGABDIAN KESEHATAN, 2023)
Premarital sexual behavior is adolescent sexual behavior that is carried out without the existence of marriage ties. Usually premarital sex behavior is often done when teenagers are dating. This behavior is the result of biological development that encourages sexual desire. According to WHO around the world every year about 40-60 million people have free sex, in the world it is estimated that 1.2 billion around 1/5 of the world's population are pregnant out of wedlock. There are 3 (three) implementation methods that will be carried out during counseling on the Perspective of Nursing and Islamic Religion on the Prevention of Free Sex Behavior in Adolescents. In order to know that counseling can be received and easily carried out by students. bearing in mind the target of youth counseling is around the age of 12-15 years, the language and actions taken must be easy to understand and not mean to offend any party. The stages that will be carried out are assessment, counseling related to the Perspective of Nursing and Islamic Religion on the Prevention of Free Sexual Behavior in Adolescents, intervention, and reassessment after conducting counseling. This activity will be held in January 2023 for youth. The counseling material provided includes the concept of the perspective of nursing science and Islamic law on free sex in adolescents, definitions, causes, impacts, and Islamic law on free sex. The result of this activity is that teenagers are able to know the dangers of free sex, know how to prevent it and know Islamic law against free sex. Achievement of good health education, where adolescents understand the challenges of free sex and free sex laws in general and the efforts made to prevent free sex. This community service provides many benefits for all youth participants as well as resource persons. The result is an increase in knowledge about healthy reproductive health in adolescents and free sex that occurs in today's youth. After understanding and increasing this knowledge, it is hoped that there will be awareness of the importance of maintaining healthy reproductive health in adolescents and being able to apply the knowledge they receive in everyday life and can become a transfer of knowledge to other adolescents. Teachers, especially counseling teachers, should further enhance their role as counselors for students who have problems regarding reproductive health, especially regarding sex and myths in sexual behavior